An Analysis Of Individual Factors, Occupational Factors, And Outstanding Factors Affecting Work Stress On Women Nurses In Inpatient Rooms Of Sibolga Public Hospital - Muhammad Syahrullah Pohan; Chrismis Novalinda Ginting; Karmila br Kaban (International Journal of Health and Pharmaceutical (IJHP), 2022)
Health nursing services in hospitals are one of the most important and goal-oriented services that focus on implementing professional nursing care according to nursing standards, depending on how nurses perform in hospitals in applying nursing care standards. Job stress is a phenomenon that affects employees differently, in different work contexts. A clean work environment will make nurses work more enthusiastically and vice versa. Job stress causes nurses to lose the ability to control it. The purpose of this study was to determine the description of individual factors, work, outside work, and work stress on female nurses in the inpatient room of Sibolga Public Hospital. The type of research used is quantitative research with analytical design through a cross-sectional approach. The population and samples used were 95 female nurses who served in the inpatient ward of the Sibolga Hospital. The results showed that individual factors, work, and outside work had a significant influence on work stress on female nurses in the inpatient room at Sibolga Hospital.